ZBTB20 is required for anterior pituitary development and lactotrope specification - Dongmei Cao (Nature Portfolio, 2016)
The pituitary is a complex structure with the anterior lobe containing five specialized cell types secreting different hormones. Here Cao et al. unravel a role for ZBTB20 in pituitary development and specifically in lactrotrope specification.